Spike in peptic ulcer disease in pregnancy in a rural community of Enugu state, southeast Nigeria: is this an epidemic? - Umegbolu, Emmanuel I. (International Journal Of Community Medicine And Public Health, 2022)
Background: Pregnancy is said to increase susceptibility to Helicobacter pylori (H. pylori) infection, probably due to decreased cell-mediated cytotoxic immune response. Despite this, evidence from epidemiological studies suggest an alleviation of peptic ulcer disease (PUD) during pregnancy. One study found the incidence of PUD among pregnant women to be as low as 0.005-0.03%. The present study aimed to determine the incidence of PUD in women who attended ante-natal clinic in Cottage Hospital Inyi, Oji River Local Government Area (LGA), Enugu State, in 2021. Methods: This was a cross-sectional study conducted with 435 pregnant women, aged 18- 40 years in 2021 in Inyi, Oji River LGA of Enugu State, Southeast Nigeria. Through purposeful sampling, 57 women were selected. From each of these patients, a stool sample was collected and examined using immunochemical fecal occult blood test. A horizontal line on the test strip signified a positive result, while its absence negative result. Data were analysed as proportion and Chi- square using MaxStat (version 3.6) statistical software. P value ≤0.05 was considered significant. Results: The incidence of PUD in the pregnant women was 13%; 4.8% in primigravidae, and 8.2% in multigravidae. The association between PUD and parity was not significant (p value =0.89). Conclusions: The incidence of PUD in pregnancy (13%) was much higher than ever had been reported in the past, being slightly higher in multigravidae than primigravidae. Health education on lifestyle modification and environmental sanitation could help in tackling this problem.